FANTOM enters 20th year: expansion of transcriptomic atlases and functional annotation of non-coding RNAs. Issue Volume 49:Issue D1(2021) (19th November 2020) - Abugessaisa, Imad; Ramilowski, Jordan A; Lizio, Marina; Severin, Jesicca; Hasegawa, Akira; Harshbarger, Jayson; Kondo, Atsushi; Noguchi, Shuhei; Yip, Chi Wai; Ooi, Jasmine Li Ching; Tagami, Michihira; Hori, Fumi; et al.
Abstract: The Functional ANnoTation Of the Mammalian genome (FANTOM) Consortium has continued to provide extensive resources in the pursuit of understanding the transcriptome, and transcriptional regulation, of mammalian genomes for the last 20 years. To share these resources with the research community, the FANTOM web-interfaces and databases are being regularly updated, enhanced and expanded with new data types. In recent years, the FANTOM Consortium's efforts have been mainly focused on creating new non-coding RNA datasets and resources. The existing FANTOM5 human and mouse miRNA atlas was supplemented with rat, dog, and chicken datasets. The sixth (latest) edition of the FANTOM project was launched to assess the function of human long non-coding RNAs (lncRNAs). From its creation until 2020, FANTOM6 has contributed to the research community a large dataset generated from the knock-down of 285 lncRNAs in human dermal fibroblasts; this is followed with extensive expression profiling and cellular phenotyping. Other updates to the FANTOM resource includes the reprocessing of the miRNA and promoter atlases of human, mouse and chicken with the latest reference genome assemblies. To facilitate the use and accessibility of all above resources we further enhanced FANTOM data viewers and web interfaces. The updated FANTOM web resource is publicly available at https://fantom.gsc.riken.jp/ .